Maternity & gynecology care : the nurse and the family - Bobak, Irene M.; Jensen, Margaret Duncan ;Lowdermilk, Deitra Leonard (St. Louis, Missouri : Mosby Elsevier, 1993)
Provides comprehensive, family-centred coverage of perinatal and women's health nursing. This edition features expanded coverage on common gynaecological problems and includes a new chapter on women's health promotion and screening.
Unit 1: Foundations for contemporary practice -- Unit 2: Normal pregnancy -- Unit 3: Normal childbirth -- Unit 4: Normal newborn -- Unit 5: Normal postpartum -- Unit 6:Complications of childbearing
Includes bibliographical references.
Keywords: MATERNITY NURSING